Downregulation of miR‐181b in mouse brain following ischemic stroke induces neuroprotection against ischemic injury through targeting heat shock protein A5 and ubiquitin carboxyl‐terminal hydrolase isozyme L1. Issue 10 (30th July 2013) - Peng, Zhifeng; Li, Jiefei; Li, Yun; Yang, Xuan; Feng, Sujuan; Han, Song; Li, Junfa
<x xml:space="preserve">Abstract</x> Understanding the molecular mechanism of cerebral hypoxic preconditioning (HPC)‐induced endogenous neuroprotection may provide potential therapeutic targets for ischemic stroke. By using bioinformatics analysis, we found that miR‐181b, one of 19 differentially expressed miRNAs, may target aconitate hydratase (ACO2), heat shock protein A5 (HSPA5), and ubiquitin carboxyl‐terminal hydrolase isozyme L1 (UCHL1) among 26 changed protein kinase C isoform‐specific interacting proteins in HPC mouse brain. In this study, the role of miR‐181b in oxygen–glucose deprivation (OGD)‐induced N2A cell ischemic injury in vitro and mouse middle cerebral artery occlusion (MCAO)‐induced cerebral ischemic injury in vivo, and its regulation of ACO2, HSPA5, and UCHL1 were further determined. We found that miR‐181b expression levels significantly decreased in mouse brain following MCAO and in OGD‐treated N2A cells. Up‐ and downregulation of miR‐181b by transfection of pre‐ or anti‐miR‐181b could negatively regulate HSPA5 and UCHL1 (but not ACO2) protein levels as well as N2A cell death and programmed cell death in OGD‐treated N2A cells. By using a T7 promoter‐driven control dual luciferase assay, we confirmed that miR‐181b could bind to the 3′‐untranslated rergions of HSPA5 and UCHL1 mRNAs and repress their translations. miR‐181b antagomir reduced caspase‐3 cleavage and neural cell loss in cerebral ischemic cortex and improved neurological deficit of mice after MCAO. In addition, HSPA5 and UCHL1 short interfering RNAs (siRNAs) blocked anti‐miR‐181b‐mediated neuroprotection against OGD‐induced N2A cell injury in vitro. These results suggest that the downregulated miR‐181b induces neuroprotection against ischemic injury through negatively regulating HSPA5 and UCHL1 protein levels, providing a potential therapeutic target for ischemic stroke. © 2013 Wiley Periodicals, Inc.